2sinx+cosx

2sinx + cosx = cosx - sinx

Expert answered|IfNotSo|Points 4269|

Question

Asked 9/25/2010 2:12:10 AM

Updated 353 days ago|6/26/2023 10:40:03 AM

1 Answer/Comment

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Rating

3

Solution:

To find a solution for the expression 2sin(x) + cos(x), we can use trigonometric identities to simplify it.

Let's rewrite the expression using the identity sin(x) = cos( /2 - x):

2sin(x) + cos(x) = 2cos( /2 - x) + cos(x)

2cos( /2 - x) + cos(x) = 2cos( /2)cos(x) + 2sin( /2)sin(x) + cos(x)

Simplifying further using the identities cos( /2) = 0 and sin( /2) = 1, we have:

2cos( /2)cos(x) + 2sin( /2)sin(x) + cos(x) = 2(0)cos(x) + 2(1)sin(x) + cos(x)

0 + 2sin(x) + cos(x) = 2sin(x) + cos(x)

Therefore, the solution is 2sin(x) + cos(x).

To find a solution for the expression 2sin(x) + cos(x), we can use trigonometric identities to simplify it.

Let's rewrite the expression using the identity sin(x) = cos( /2 - x):

2sin(x) + cos(x) = 2cos( /2 - x) + cos(x)

2cos( /2 - x) + cos(x) = 2cos( /2)cos(x) + 2sin( /2)sin(x) + cos(x)

Simplifying further using the identities cos( /2) = 0 and sin( /2) = 1, we have:

2cos( /2)cos(x) + 2sin( /2)sin(x) + cos(x) = 2(0)cos(x) + 2(1)sin(x) + cos(x)

0 + 2sin(x) + cos(x) = 2sin(x) + cos(x)

Therefore, the solution is 2sin(x) + cos(x).

Added 353 days ago|6/26/2023 10:40:03 AM

This answer has been confirmed as correct and helpful.

39,223,775

questions answered

There are no comments.